Copper and nickel composite carbon catalysts prepared from olive husks on the adsorption process of phenol and p-nitrophenol: comparative theoretical study via an analytical model. (2024)
The adsorption of phenols and p-nitrophenols on prepared activated carbons is one of the most important wastewater treatment processes. The four catalysts (RC, AC, Ni-AC) were prepared from the olive shell and characterized by Fourier transfer infrared spectroscopy, scanning electron microscopy, N2 adsorption/desorption, zero charge point, and X-ray diffraction, which confirmed the success of the process. The results showed that the impregnation improved the adsorption capacity of the carbon material. For p-nitrophenol, an increase from 90 mg/g to 156 mg/g was observed for Ni-AC and 143 mg/g for Cu-AC. Analysis of the model parameters showed that the adsorbate particles have a non-parallel exposure with respect to the surface of the nickel-bridged activated biochar and that each functional group of the adsorbent binds to several particles simultaneously. Finally, the adsorption forces suggest that physical forces, including hydrogen bonding and van der Waals forces, are likely to be involved in the adsorption, as indicated by values below 22 kJ/mole. The results of adsorption tests of phenol and p-nitrophenol by the prepared materials showed that these materials could replace other more expensive adsorbents.